(untitled) (Bangladesh Journal of Medicine, 2019)
Oral polio vaccine (OPV) has served as the cornerstone of polio eradication efforts over the past 30 years, trivalent inactivated polio vaccine (IPV) has re-ascended to prominence in the past year, now acting as the sole source of protective immunity against type 2 poliovirus in routine immunization programmes. The Polio Eradication and Endgame Strategic plan 2013–2018, developed by the Global Polio Eradication Initiative (GPEI) outlines the phased removal of OPVs, starting with type 2 poliovirus–containing vaccines and introduction of inactivated polio vaccine in routine immunization to mitigate against risk of vaccine-associated paralytic polio and circulating vaccine-derived poliovirus. Bangladesh J Medicine Jan 2020; 31(1) : 22-28